PENGARUH PERSEPSI SISWA TENTANG PEMBELAJARAN BERBASIS ONLINE SERTA BIMBINGAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA AKIBAT PANDEMI COVID-19 DI LINGKUNGAN POHDANA GERUNG LOMBOK BARAT - Meiyana Diah Lestari; Hadi Kusuma Ningrat; Alfina Mizriaty (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2021)
The study aims to determine the effect of student’s perceptions of online learning on student learning motivation on during the covid-19 pandemic. The population in this study were 26 students in the Pohdana environment of Gerung west Lombok. The sample was 26 students in the Pohdana environment of Gerung west Lombok. Data collection using a questionnaire instrument. Data analysis using simple regression analysis. The results showed that (1) there was an effect of student’s perceptions of online learning on student learning motivation during the covid-19 pandemic which was known that calculation t value was greater than the t table, namely 7.9609 > 2.064 and the sig value <0.05 (0.000<0.05) then Ha is accepted. Thus it can be said that the influence of student perceptions about online learning on student learning motivation during the covid-19 pandemic in the Gerung Pohdana environment west Lombok.